Social Communications in the Post-Pandemic ‘New Normality’ - Wojciech SŁOMSKI (Communications of International Proceedings, 2021)
The worldwide pandemic of COVID-19 has impacted on the all areas of human life. It is still a complicated task to evaluate the changes, coming in the aftermath of the pandemic with all its waves and virus strains. Mostsocial, economic and political changes are considered to be irreversible to a certain extent. New conditions require some reconsideration of what is ‘normal’ in the way of life and human behavior. The changes of far-reaching importance will presumably constitute ‘new normality’. The paper focuses on a significant aspect of the coming post-pandemic ‘new normality’ that is social communications, underlying social interactions, social cognition, social adaptation and other social phenomena and epiphenomena. Contemporary social communications play the key role of connecting link in economic, social and political relations. That is why an insight into social communications could help us better see the whole picture of ‘new normality’. The identified trends in social communications such as virtualization, anonymity, interactivity, fictitiousness, distortion and fragmentation of communicative space, extreme specification, network group particularism, are not exclusively caused by the pandemic restrictions. The trends have appeared much earlier and become apparent before the pandemic. The restrictions, having been introduced to stop this infectious disease, have acted as an accelerator for the trends described below. The contemporary changes in the area of social communications have been triggered by social distancing, distant way of working, distant communicative events etc. It can be determined as ‘threshold effect’ typical for some long-term social processes with a long latent period.
Keywords: New Normality; Social Communications; COVID-19 Pandemic; Virtualization.